A New Chemical Approach to Human ABO Histo-Blood Group Type 2 Antigens - Hara, Atsushi (Molecules, 2013)
A new chemical approach to synthesizing human ABO histo-blood type 2 antigenic determinants was developed. N-Phthaloyl-protected lactosaminyl thioglycoside derived from lactulose via the Heyns rearrangement was employed to obtain a type 2 core disaccharide. Use of this scheme lowered the overall number of reaction steps. Stereoselective construction of the α-galactosaminide/galactoside found in A- and B-antigens, respectively, was achieved by using a unique di-tert-butylsilylene-directed α-glycosylation method. The proposed synthetic scheme provides an alternative to existing procedures for preparing ABO blood group antigens.